From Head‐hunter to Organ‐thief: Verisimilitude, Doubt, and Plausible Worlds in Indonesia and Beyond. Issue 1 (20th September 2016) - Bubandt, Nils
Abstract : In the last few years, occult head‐hunters – elusive figures that have haunted communities and the public imagination in Indonesia since at least colonial times – appear to have adopted a novel and troubling tactic. Instead of decapitating their victims and using the heads in construction rituals as they are said to have conventionally done, head‐hunters are now allegedly harvesting their victims' organs to sell them on the global market of body parts. Based on a comparison of ethnographic material from North Maluku, a province in the eastern part of Indonesia, and news reports in regional and national papers, I trace how accounts about headhunting have morphed with narratives about organ theft. I argue that this plasticity is not a merely a change in symbolic ideas of the occult that reflects changing political and economic realities. Rather, I propose that their turn to organ theft enrols head‐hunters in a contemporary and global 'travelling package' that includes and entangles organ trafficking practices, media accounts, political imaginaries, and social anxieties within the same field of reality and possibility, a field of verisimilitude in which fiction and fact, rumour and reality, are fundamentally blurred. The article proposes a 'more‐than‐representational' approach to the organ‐stealing head‐hunter that sees him not just as a representation of particular political and historical circumstances but as a co‐producer of these circumstances, of particular political worlds and their attendant scales of anxiety. This approach, I argue, challenges the epistemological distinction between symbolic representation and political reality that informed (but also incommoded) the analyses of headhunting rumours in the 1980s and 1990s – and that continues to inform anthropological analyses of 'the occult' more generally.